Tissue-based skin prick test extracts from Atlantic salmon containing occupationally relevant allergens - Elda, Inga; Grgic, Miriam; Stensvåg, Klara; Bang, Berit (Frontiers in Allergy, 2025)
IntroductionDiagnosis of salmon allergy often includes skin prick testing using commercially available extracts. Multiple studies have shown that these may contain highly variable amounts of important allergens. In this study we aimed to produce skin prick test extracts containing salmon allergens relevant to the occupational exposure situation. The extracts were characterized with respect to the presence of known salmon allergens. The effect of heat-treatment on the antibody-binding of allergens was also assessed.MethodAllergenic proteins were extracted from muscle, skin, and outer mucus coating from Atlantic salmon (Salmo salar). Electrophoresis was used for protein separation with subsequent silver staining and immunoblotting for the detection of known allergenic proteins with antibody-binding activity to commercially available antibodies. The identity of allergens was confirmed by mass spectrometry.ResultsOur extraction methods were successful in detecting the allergenic proteins aldolase, collagen, enolase, and parvalbumin from muscle, skin, and outer mucus coating from Atlantic salmon. Our work also demonstrates that these allergens have various tolerance towards heating.ConclusionBy using multiple fish tissues for extraction, we were able to produce skin prick test extracts containing allergens of presumed relevance in diagnosis of work-related sensitization.